PROSES METAKOGNISI MAHASISWA DENGAN TIPE ADVERSITY QUOTIENT (AQ) QUITTERS DALAM MEMECAHKAN MASALAH MATEMATIKA - Rosana Setyaningsih (Fakultas Keguruan dan Ilmu Pendidikan Universitas Kristen Satya Wacana, 2018)
ABSTRACT Metacognition is one of the important things in supporting one's success in solving mathematics problems because by using metacognition when solving problems, effective problem solving will be obtained. Metacognition is one's awareness of his own thought process. In dealing with a problem, it will be influenced by Adversity Quotient (AQ), namely intelligence in facing difficulties and changing barriers into opportunities for success. This research is a qualitative descriptive study. The subjects in this study were a Satya Wacana Christian University Mathematics Education student who had the AQ type of quitters. Quitters are a type of human who easily gives up in the face of difficulties. The results showed that the metacognition process experienced by the subject included metacognition awareness, evaluation, and regulation. In addition, metacognition also helps the subject to make thoughts and problem solving strategies more effective.